KONTRIBUSI GURU DALAM PRAKTIK MANAJEMEN PENDIDIKAN: ANTARA PERAN INTRUKSIONAL DAN PARTISIPASI ORGANISASI - Malika Dwi Amelia; Siti Ropiatul Adawiyah; Yunisa (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Teachers play a strategic role in the implementation of educational management, both through their instructional duties in the classroom and their participation in school organisations. This journal examines the contribution of teachers from these two perspectives, emphasising the reciprocal relationship between pedagogical competence and managerial capacity. Teachers are not only actors in learning, but also agents of change, academic leaders, managers of organisational culture, and implementers of educational policy. Through theoretical analysis and literature review, this journal shows that improving the quality of education is greatly influenced by the balance and collaboration between teachers' roles in the school context. This journal also provides an in-depth understanding of the challenges and strategies for strengthening the role of teachers in modern educational management.